The Utility of a “Second-Look” Debridement Following Endonasal Skull Base Surgery in the Pediatric Population - Chang, Michael T.; Huang, Alice E.; Quon, Jennifer L.; Fernandez-Miranda, Juan C.; Wen, Christopher Z.; Eide, Jacob G.; Kshirsagar, Rijul S.; Qian, Z Jason; Nayak, Jayakar V.; Hwang, Peter H.; Adappa, Nithin D.; Patel, Zara M. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Background Sinonasal debridement is typically performed in the weeks following endonasal skull base surgery (ESBS). In the pediatric population, this second-look procedure may require general anesthesia; however, there is currently little evidence assessing the benefit of this practice.Methods This was a multicenter retrospective study of pediatric patients (age <18 years) undergoing a planned second-look debridement under general anesthesia following ESBS. Intraoperative findings, interventions performed, and perioperative complications were reviewed. Multivariate regression analysis was performed to identify associations between intraoperative findings and clinical factors.Results We reviewed 69 cases of second-look debridements (age mean 8.6 ± 4.2 years, range: 2–18 years), occurring a mean of 18.3 ± 10.3 days following ESBS. All abnormal findings were noted in patients age ≤12 years. Synechiae were noted in 8.7% of cases, bacterial rhinosinusitis in 2.9%, and failed reconstruction with cerebrospinal fluid leak in 4.5% (two cases of flap malposition and one case of flap necrosis). All failed reconstructions were noted following expanded endonasal cases for craniopharyngioma, and in each case, a revision reconstruction was performed during the second-look surgery. Synechiae were not significantly associated with younger age, revision cases, or cases with reconstructive flaps. There were no perioperative complications.Conclusion Second-look debridement under general anesthesia may be useful in the identification and intervention of sinonasal pathology following endoscopic skull base surgery, particularly in children ≤12 years old or those with pedicled flap reconstructions. Larger controlled studies are warranted to validate this practice and refine indications and timing of this second procedure.
Keywords: skull base; endoscopic; quality of life; sinonasal outcomes; postoperative care